Lobaplatin-based prophylactic hyperthermic intraperitoneal chemotherapy for T4 gastric cancer patients: A retrospective clinical study - Zhong, Yuxin; Kang, Wenzhe; Hu, Haitao; Li, Weikun; Zhang, Jing; Tian, Yantao (Frontiers in Oncology, 2023)
Objective: To explore the clinical efficacy of lobaplatin-based prophylactic hepatic intraperitoneal chemotherapy (HIPEC) for patients with T4 gastric cancer after surgery and to evaluate its impact on survival. Materials and Methods: Data on patients with T4 gastric cancer who underwent radical gastric resection between March 2016 and August 2017 were collected from the National Cancer Center and Huangxing Cancer Hospital. According to whether lobaplatin-based HIPEC was applied, all enrolled patients were divided into two groups. Results: A total of 106 patients were included in this study; among them, 51 patients underwent radical gastric resection plus prophylactic HIPEC, and 55 patients underwent radical gastric resection only. The baseline characteristics were well balanced between the two groups. The postoperative platelet counts in the HIPEC group were significantly lower than those in the non-HIPEC group (P < 0.05); however, we did not observe any occurrences of serious bleeding in the HIPEC group. There were no significant differences in the postoperative complication rates between the two groups (P > 0.05). The postoperative (1 month) CEA, CA19-9, and CA72-4 levels in the HIPEC group were significantly decreased in the HIPEC group (P < 0.05). At a median follow-up of 59.3 months, 3 (5.5%) patients in the HIPEC group experienced peritoneal recurrence, and 10 (18.2%) patients in the non-HIPEC group experienced peritoneal recurrence (P < 0.05). Both groups had comparable 5-year overall survival (OS) rates (41.1% HIPEC group vs. 34.5% non-HIPEC group, P = 0.118). The 5-year disease-free survival was significantly higher in the HIPEC group than in the non-HIPEC group (28.6% versus 39.7%, p = 0.046). Conclusions: Lobaplatin-based prophylactic HIPEC is feasible and safe for patients with T4 gastric cancer and does not increase postoperative adverse effects. The use of HIPEC showed a significant decrease in the incidence of local recurrence rates and blood tumor marker levels. The 5-year disease-free survival was significantly higher in the HIPEC group; however, the 5-year OS benefit was not found in T4 stage patients.